Hubungan Tingkat Penghasilan Orangtua dengan Kejadian Stunting pada Balita usia 0 – 59 Bulan - Nabila Fasiha Firmania; Dony Septriana; Ahmad Djojosugito (Bandung Conference Series: Medical Science, 2023)
Abstract. According to the World Health Organization (WHO) stunting is a chronic growth disorder which is the main cause of toddlers being short compared to children of their age. This disease does not only have an impact on the physical, but affects other aspects such as cognitive decline, inhibited physical activity and is more susceptible to degenerative diseases. According to the 2018 National Health Research (Riskesdas), one of the causes of stunting is the level of parental income which can affect children's growth due to inadequate nutritional intake. Based on this description, the problems in this study are formulated as follows: (1) What is the income level of parents of toddlers with stunting? (2) What is the incidence of stunting in toddlers at the Soreang Health Center? (3) What is the relationship between parents' income levels and the incidence of stunting in toddlers aged 0-59 months at the Soreang Health Center? The researcher used an analytic observational method with a cross-sectional approach which was carried out at the Soreang Community Health Center in Bandung Regency using a parental income level form. A sample of 48 respondents used the consecutive sampling method with bivariate and univariate analysis techniques with the chi-square test. The results of the study show that parents have a low income level of 31% and toddlers who experience stunting reach 45%. The results of the statistical analysis show that there is a relationship between parents' income levels and stunting toddlers (p value = <0.001). The conclusion from this study is that the level of parental income influences the incidence of stunting in toddlers aged 0-59 months. Abstrak. Menurut World Health Organization (WHO) stunting adalah gangguan pertumbuhan kronis yang menjadi penyebab utama balita menjadi pendek dibandingkan dengan anak seumurnya. Penyakit ini tidak hanya berdampak pada fisik, tetapi mempengaruhi aspek lain seperti penurunan kognitif, aktivitas fisik terhambat dan lebih rentan terpapar penyakit degenerative. Menurut Riset Kesehatan Nasional (Riskesdas) 2018 salah satu penyebab stunting adalah tingkat penghasilan orangtua yang dapat mempengaruhi pertumbuhan anak karena asupan nutrisi yang tidak memadai. Berdasarkan uraian tersebut, maka permasalahan dalam penelitian ini dirumuskan sebegai berikut: (1) Bagaimana tingkat penghasilan orangtua pada balita dengan kejadian stunting? (2) Bagaimana kejadian stunting pada balita di Puskesmas Soreang? (3) Bagaimana hubungan tingkat penghasilan orangtua terhadap kejadian stunting pada balita usia 0 – 59 buan di Puskesmas Soreang?. Peneliti menggunakan metode obervasional analitik dengan pendekatan cross-sectional yang dilakukan di Puskesmas Soreang Kabupaten Bandung dengan menggunakan formulir tingkat penghasilan orangtua. Sampel sebanyak 48 responden menggunakan metode consecutive sampling dengan teknik analisis bivariat dan univariat dengan uji chi-square. Hasil penelitian menunjukan bahwa tingkat penghasilan rendah pada orangtua 31% dan balita yang mengalami stunting mencapai 45%. Hasil analisis statistik diketahui ada hubungan tingkat penghasilan orangtua dengan balita stunting (p value = <0,001). Simpulan dari penelitian ini adalah tingkat penghasilan orangtua berpengaruh terhadap kejadian stunting pada balita usia 0 – 59 bulan.